Pengaruh Kecerdasan Adversitas dan Rasa Percaya Diri Terhadap Kemampuan Berpikir Kritis Matematika Siswa MTs Negeri di Jakarta Selatan - Siti Nurjanah (Nusantara: Jurnal Pendidikan Indonesia, 2026)
Purpose – This study was conducted to address the issue of low mathematical critical thinking skills among students, a subject often perceived as challenging, as evidenced by the decline in national examination scores. The primary objective is to analyze the influence of internal factors, specifically adversity quotient and self-confidence on the mathematical critical thinking skills of students at State Madrasah Tsanawiyah (MTsN) in South Jakarta. Methods – This research employed a survey method utilizing path analysis. The population consisted of 614 students, with a sample of 86 respondents selected through simple random sampling using the Slovin formula. Data was collected via Likert-scale questionnaires for the adversity quotient and self-confidence variables, while mathematical critical thinking skills were measured using a test instrument. Data analysis was performed using SPSS version 22. Findings – The results demonstrate a positive and significant influence among the tested variables. Quantitative findings reveal that self-confidence has a larger direct effect (0.444) on critical thinking skills compared to the direct effect of adversity quotient (0.323). However, adversity quotient plays a crucial role in shaping student self-confidence, with a strong path coefficient of 0.688. Additionally, a significant indirect effect was found between adversity quotient and mathematical critical thinking skills mediated by self-confidence.Research Implications – Practically, these findings suggest that schools should integrate the development of a resilient mindset (AQ) as a foundation to bolster self-confidence, thereby accelerating students' critical analytical abilities in mathematics.